An Analysis of the Influence of Leadership, Work Motivation and the Working Environment on Employee Performance at Bengkel 24 Project in Medan - Achmad Surya Arif; Ikhah Malikhah; Daud Arifin (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of leadership, work motivation, and work environment on employee performance in Workshop 24 Project Medan with a quantitative approach through a survey of 45 respondents and multiple linear regression analysis (SPSS 22). The results of the partial test showed that leadership had no significant effect on performance (β = 0.187; sig. 0.135 > 0.05). Work motivation had a positive and significant effect and was the most dominant variable (β = 0.528; sig. 0.000 < 0.05). The work environment had a significant effect on the negative direction (β = −0.284; sig. 0.042 < 0.05). Simultaneously, all three variables had a significant effect on performance (F = 20.028; sig. 0.000 < 0.05) with an Adjusted R² value of 0.565, which means that 56.5% of the variation in performance was explained by the model. It was concluded that work motivation is the main factor in improving performance, while the work environment needs special attention and leadership has not shown a significant influence.